Exploring Women’s Transformative Learning and Community Building through Practicing Martial Arts to Disrupt Gendered and Hetero-Patriarchal Norms - Dobrich, Emily (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2024)
This article explores the potential for martial arts to support transformation and community building for women. Findings indicate women can derive many individual benefits from learning martial arts. Yet, the benefits must extend beyond the individual level to create social change. Based on an evaluation of literature on women’s experiences learning martial arts, I use my perspective as an adult education researcher and a feminist lens to propose creative approaches to supporting women in learning martial arts. Supporting women in learning martial arts requires promoting creativity and invention in practice. Feminist new materialism, transformative learning theory, and communities of practice are the theories that guide the direction of this article. The major contribution of this article is to offer creative approaches for imagining a feminist praxis through martial arts that could foster learning environments that encourage self-determination and build social support and resistance to hetero-patriarchal power and gender inequity, which has relevance to broader educational settings and communities.